Risk transmissions between regional green economy indices: Evidence from the US, Europe and Asia. (15th December 2022) - Gunay, Samet; Muhammed, Shahnawaz; Elkanj, Nasser
Abstract: This paper examines the risk transmissions across the green economy indices of three major regions which include US, Europe and Asia. The econometric analyses are conducted using DCC-GARCH and TVP-VAR connectedness approach to evaluate potential spillover effects within the context of oil and gold. Results indicate that green economy indices of US-Europe exhibit the greatest time-varying correlations among the three pairs during much of 2010–2022 consistent with that of the general equity market. However, co-movements during the COVID-19 pandemic period seem to display a change in pattern for green economy indices. The strength of the co-movements between the US and Europe displayed a declining trend, while that between US and Asia was strengthened, suggesting greater interdependence between these two markets. TVP-VAR connectedness analysis revealed that US and Europe dominate the transmission of the shocks across the years in the green economy, similar to that of the equity markets. However, during the pandemic a pronounced shift occurred in green economies when considering the risk transmissions within the context of commodities: oil and gold. While Asian green economy index was persistently a receiver of risk transmission from oil unlike the other two regions, since pandemic, oil displayed an asymmetric effect and has become the net transmitter of risk in negative returns of the green economies of US and Europe. This may reflect the diversion in environmental policies of the two regions in the recent past, and point to the dominance of energy sector in the green economy. These findings have substantial implications for the development of green economy policies and from an investment perspective.